Syrian Women Refugees: Coping with indeterminate liminality during forcible displacement. Issue 10 (October 2022) - Alkhaled, Sophie; Sasaki, Innan
This paper examines how forcibly displaced people cope with prolonged liminality through identity work. Our paper is based on a longitudinal multiple case study of women refugees who fled Syria and experienced liminality in Amman-Jordan, the Zaatari Refugee Camp in Jordan and the United Kingdom. We contribute to the liminality literature by demonstrating how forcibly displaced people respond to extreme structural constraints and maintain cognitive control over their sense of self during liminality with an end date that is unknown. We develop the concept of liminality by illustrating how the actors were pushed into a state of 'indeterminate liminality' and coped by co-constructing it through three forms of identity work – recomposing conflicting memories, reclaiming existence and repositioning tradition. This enabled them to stretch the boundaries of indeterminate liminality, symbolically restore their familiar past and narratively construct a meaningful future.